An Eigenmode Correlation‐Based Algorithm for Approaching Antenna Optimal Currents With Multiple Feeds. Issue 5 (16th May 2020) - Zhang, Wei‐Quan; Zhang, Guo‐Yang; Wang, Bing‐Zhong; Xiong, Jiang
Abstract: A feeding algorithm has been proposed for the excitation of the optimal electric current of Rayleigh quotient form optimization problems. Modal weighting coefficients of the corresponding generalized eigenvalue problem are calculated to form the correlation information between the desired and all other unwanted modes. Based on this information, multiple feeds are arranged to approximate the desired current distributions. The eigencurrent distribution is also utilized for some shape modification to the radiator for a possible feed number reduction. Three canonical optimization problems for electrically small antennas, minimum Q, maximum G / Q, and maximum G are studied and discussed. Several numerical examples with a certain arbitrary shape and electrical size are given. With the proposed feeding algorithm, calculated and simulated current distributions and performance indices are close to the theoretical optimum solution. Finally, a practical feeding network design for a classic characteristic mode problem is shown as a validation. Key Points: This paper proposes an algorithm for fast determining feeding of a generalized eigenvalue problem‐based optimal current distribution An efficient collection of eigenmode correlation is utilized for the multifeed deployment, and a physical intervention is also introduced Several examples of ESA canonical optimization problems have been studied, and a practical feeding network design is shown as validation